Forever young: the first seventy years of ferrocene - Štěpnička, Petr (Dalton transactions (Cambridge, England, 2022)
The discovery of ferrocene, [Fe(η5-C5H5)2], seventy years ago has significantly influenced chemical research and provided a key impetus for establishing and rapidly expanding organometallic chemistry, which has continued at a rapid pace until now. Over the years of intensive research, the ferrocene unit has been recognised as an extremely versatile platform for ligand design, materials research, and medicinal and analytical chemistry as well as many other research fields. Such wide applications of ferrocene and its derivatives are obviously rooted in the unique combination of the properties of the ferrocene moiety, which exhibits high chemical stability but is amenable to diverse synthetic modifications, has well-defined and highly specific steric properties, and displays defined and tuneable redox behaviour. The unrelenting research activity focused on ferrocene compounds and their widespread applications can be expected to continue even in the future to yield more attractive results in terms of both novelty and function.
Keywords: oxidace-redukce; metaloceny; Metallocenes; Oxidation-Reduction